Pemodelan Persamaan Struktural Kemampuan Akademik dan Karakteristik Individu dalam Mengidentifikasi Ketertarikan Siswa Kelas XII dalam Memilih Perguruan Tinggi Negeri - Sopbaba, Merlina; Simarmata, Justin Eduardo; Klau, Kondradus Yohanes (Jambura Journal of Probability and Statistics, 2024)
State universities represent a primary option for prospective students aspiring to pursue higher education. During the selection process of a state university, prospective students are influenced by various factors, including academic prowess, individual traits, and personal considerations pertinent to their chosen state university. This study was conducted among 59 twelfth-grade students at SMA Kristen Petra Kefamenanu during the academic year 2023-2024. The methodological framework of structural equation modeling (SEM) was utilized to investigate the interrelationships among these variables. The analysis revealed that students' academic aptitude, comprising elements such as self-assurance, scholastic achievements, active participation, and innovative thinking capabilities, exerts a significant impact on their inclination towards selecting state universities, with a path coefficient of 0.40. Moreover, individual attributes such as autonomy, creativity, integrity, courage, and perseverance also demonstrate a substantial influence, yielding a path coefficient of 0.84 on the inclination towards selecting state universities. These findings underscore the pivotal roles played by both academic capabilities and individual attributes in the decision-making process surrounding state university selection. These findings indicate that both academic ability and individual characteristics play important roles in the decision to choose state universities. These results can serve as a guide for educational institutions and parents to better understand the factors influencing students' decisions in choosing higher education institutions and can help in developing more effective new student admission strategies.